PEMBERIANTRICHOKOMPOSLIMBAHJAGUNG BERFORMULASI DENGANDOSIS YANGBERBEDA UNTUKPERTUMBUHANBIBITKELAPASAWIT (Elaeis guineensisJacq.) DI PEMBIBITANAWAL - Pujianto Pujianto; Hapsoh Hapsoh; Muhammad Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Production of oil palm crops can be kept stable by replanting, by replacing unproductive crops with new crops and using good quality seeds. The use of maize trichocompos is formulated as organic fertilizer, can be done to increase the growth of oil palm seedlings. The purpose of this study was to investigate the effect of Trichocompos maize waste formulations and to obtain a good dose for the growth of oil palm seedlings in early seeding. This research was conducted by experiment using Randomized Complete Design, with 5 treatments and 4 replications consisting of: T1 = 10 g Trichokompos, T2 = 15 g Trichokompos, T3 = 20 g Trichokompos, T4 = 25 g Trichokompos, T5 = 30 g Trichokompos. Data from the observations obtained, analyzed using analysis of variance and conducted a further test Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results of this study indicate that the administration of several maize trichocompos doses formulated can increase the height of seedlings, root volume and dry weight of oil palm seedlings in early seedlings. Trichokompos of maize waste formulated with a dose of 30 g / plant has the best ability to increase the growth of oil palm seedlings in early seeding.Keywords: Palm oil, Trichocompost of maize wastes formulated, Early breeding